Ley de sociedades comerciales de beneficio e interés colectivo : ¿un avance para un régimen jurídico de responsabilidad social empresarial en Colombia? (2020)
In this text, the author analyzes BIC corporations under a context of corporate social responsibility or CSR. To do that, the concept of social responsibility of business is studied both in Colombia and in other countries. This will lead to conclude how the state of art in Colombia is right now. With this information, it will be analyzed if the new law brings an important advance in this regime, having to observe the positive and negative aspects of the recent regulation. This will lead to a necessary focus on the objectives of the law and its actual results. After that, the author analyzes if the incentives that these BIC stamps give to corporations are effective compared to the obligations that come with them and if the law effectively regulates some possible conflictive situations that may come with CSR.